2020
DOI: 10.1007/s13178-020-00486-2
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived Importance and Enjoyment of Sexuality in Late Midlife: Cohort Differences in the Longitudinal Aging Study Amsterdam (LASA)

Abstract: Introduction Age-related declines in multiple facets of sexuality in later life are well documented. However, most studies have been cross-sectional with data collected at one point in time, leaving questions about cohort differences and interrelated historical changes in physical health and psychosocial functioning unanswered. Methods We examined cohort differences in perceived importance and enjoyment of sexuality in late midlife using data from the Longitudinal Aging Study Amsterdam (LASA) obtained 20 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 72 publications
(109 reference statements)
4
7
0
Order By: Relevance
“…The Longitudinal Aging Study of Amsterdam (LASA) designed in a manner similar to the ELSA and found that satisfaction with sexual activity in older adults was associated with better cognitive function in several domains includingexecutive functions, verbal memory, visual memory, processing speed, and fluid intelligence. 23 Other aging studies have reported higher rates of sexual dysfunction as well as a change in sexual behaviors in persons with mild cognitive impairment (MCI) and dementia when compared to those without cognitive impairment. 24 However, strikingly, these appear to be independent of the degree of impairment, age, gender, number of years of education, number of years of illness, or medication.…”
Section: Sexual Activity In Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…The Longitudinal Aging Study of Amsterdam (LASA) designed in a manner similar to the ELSA and found that satisfaction with sexual activity in older adults was associated with better cognitive function in several domains includingexecutive functions, verbal memory, visual memory, processing speed, and fluid intelligence. 23 Other aging studies have reported higher rates of sexual dysfunction as well as a change in sexual behaviors in persons with mild cognitive impairment (MCI) and dementia when compared to those without cognitive impairment. 24 However, strikingly, these appear to be independent of the degree of impairment, age, gender, number of years of education, number of years of illness, or medication.…”
Section: Sexual Activity In Dementiamentioning
confidence: 99%
“…The Longitudinal Aging Study of Amsterdam (LASA) designed in a manner similar to the ELSA and found that satisfaction with sexual activity in older adults was associated with better cognitive function in several domains including—executive functions, verbal memory, visual memory, processing speed, and fluid intelligence. 23…”
Section: Sexual Activity In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases women become religious and developed inhibition for active sex as their children are growing up. 48 All these factors make menopausal women reluctant for sexual activities. In some her partner's wish to have regular sex and intercourse but women does not co-operate.…”
Section: Is Menopause End Of Sexual Life ???mentioning
confidence: 99%
“…It is well established that regular and active involvement in sexual activity enhances the lives of both partners long gaps (abstinence) between the sexual intercourse significantly declines sexual desire of the couples. 48 The plus point with women is that she can involve herself in sex as and when she wishes to do/ think contrary to man.…”
Section: Is Menopause End Of Sexual Life ???mentioning
confidence: 99%